Enhanced Design of Fractional Order Induction Heating System - Padmanabha Sivakumar, G.; Kannan, Umapathy (International Journal of Engineering and Technology, 2018)
Class-F3 power amplifier system (CF3AS) is capable of generating fast heat for induction Heating or Dielectric. The main objective of research is to obtain a steady output voltage using the high frequency Class-F3 amplifier for an induction heating system. The entire work carried out using the CF3AS in closed loop.Â  An uncontrolled rectifier is used to convert the AC (Alternating Current) supply into DC (Direct Current). The CF3AS converts the DC into high frequency AC. The FOPID controller is provided in the circuit to maintain the stable output voltage in the final stage. PI controlled CF3AS is used for comparing the results of FOPID based CF3AS.Â Â